Resistance to the infrastructure that governs local literacy and social practices in an English classroom. (2nd January 2023) - Sosa, Teresa; Hall, Allison H.; Latta, Mark
ABSTRACT: This work looks at how the infrastructure or conventions of practice and social arrangements govern local classroom literacy practices and how marginalized students resist the infrastructure and expose institutional change-making possibilities. Drawing from a longitudinal study, we analyzed five days of lessons that constituted a project in order to attend to aspects of instruction and activity that were indicative of the infrastructure and whether, and if so, how, students used language, body, silence, etc., to disrupt these guiding practices. The questions that guide this work are the following: What does student resistance reveal about the institutional infrastructure in this classroom? How did youth exploit the infrastructure's fissures and what does it reveal about racial wisdom? Our findings demonstrate how students navigated, negotiated, and addressed the institutional complexities that shaped this assignment and offered limited ways to navigate it. This work offers a broader understanding of what students' enactment of resistance disrupts and provides a clearer understanding of student racial wisdom.